Massive Bleeding as the First Clinical Manifestation of Metastatic Prostate Cancer due to Disseminated Intravascular Coagulation with Enhanced Fibrinolysis - Mónica Palma Anselmo; Gustavo Nobre de Jesus; João Madeira Lopes; Rui M. M. Victorino; João Meneses Santos (Case Reports in Hematology)
Disseminated intravascular coagulation (DIC) is the most frequent coagulation disorder associated with metastatic prostate adenocarcinoma. However, DIC with enhanced fibrinolysis as an initial presentation of prostate cancer is extremely rare. The appropriate treatment to control bleeding in these situations is challenging, controversial, and based on isolated case reports in the literature. A 66-year-old male presented at the emergency department with acute severe spontaneous ecchymoses localized to the limbs, laterocervical hematoma, and hemothorax. Prostate specific antigen level was 385 μg/L, bone scintigraphy revealed multiple bone metastases, and prostate biopsy confirmed adenocarcinoma (Gleason 9; 4 + 5). Laboratory investigation showed a pattern of enhanced fibrinolysis rather than the more common intravascular coagulation mechanism. Epsilon aminocaproic acid in monotherapy was initiated with a clear and rapid control of bleeding manifestations. This rare case of massive bleeding due to DIC with enhanced fibrinolysis as the first manifestation of prostate cancer suggests that in selected cases where the acute bleeding dyscrasia is clearly associated with a dominant fibrinolysis mechanism it is possible to use an approach of monotherapy with antifibrinolytics.